Listening to the Voice of the Consumer: Expanding Technology Acceptance Model for Online Transportation Context - Yudhistira, Diaz Satriavi; Sushandoyo, Dedy (School of Business and Management Institut Teknologi Bandung, 2018)
Abstract. In business, every successful innovation must be followed with commercial success. Thus, consumer acceptance is essential for technological innovation to gain success commercially. In Indonesia, Mobile Online Transportation Service (MOTS) has become phenomena in recent years. They are blooming and creating a new business opportunity as consumer acceptance is arguably high. This phenomena lead us to our question if is there any variables compatible to be added to TAM to be used in today’s context? As we know, TAM was developed in the eighties by Fred Davis, and this new mobile ICT base innovation did not exist yet. Using a literature review, this conceptual paper will compare the original TAM model with consumer review data gathered from MOTS application stores to answer our research question. As a result, we proposed an extended version of TAM. Keyword: TAM, innovation, mobile online transportation, service quality, price, relative advantage